One More Time Towards the Definitions Language Planning and Language Policy (Parliamentary Studies, 2015)
Despite the fact that the term language planning has been in use for over five decades now, its definition is not straightforward and it is frequently lumped together with the term language policy. Such use of the term language planning not only leads to confusion and misunderstanding, but also does not follow the rules of terminology standards. It can be treated as a radical relic of prescriptivism; it ignores the traditional understanding of the term and obstructs linguists’ dialogue with the general public, who understand the term language planning differently. The paper suggests the following distinction between the terms language planning and language policy: when certain choices are being made by the nation or its representatives, it is the language policy which is being formed on the basis of ideology. It is followed by the implementation of specific tasks driven by those political decisions, i.e. it is followed by language planning. In this view the policy is first and only then comes the planning of actions and, finally, implementation of the plan. Language planning is the result of language policy, its implementation, but not the other way round, i.e. the basis for language policy implementation is not language planning. Planning without policy is an activity without proper foundations.
Keywords: language policy; language planning; definitions; terminology